Clinical outcomes of varying age groups following vertical sleeve gastrectomy: a retrospective study using the 2022 Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program database in the United States - Satyam K. Ghodasara; Jana K. Elsawwah; Hyo J. Yang; Ashish Padnani; Zoltan H. Nemeth (Journal of Minimally Invasive Surgery)
Purpose: The rising rates of obesity across the United States, particularly among pediatric and elderly patients, have led to more bariatric surgeries among these populations. Previous studies have compared the outcomes between pediatric or elderly patients and adult patients, but none have studied all groups together. Therefore, we compared the outcomes of all three age groups following a laparoscopic sleeve gastrectomy. Methods : The 2022 Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program (MBSAQIP) was utilized to identify pediatric (aged 13-17 years, n = 333), adult (aged 18-65 years, n = 118,444), and elderly (aged 66-80 years, n = 5,646) patients. Analyses were performed with the adult cohort serving as the reference group. Results : Postoperatively, the elderly cohort experienced higher rates of mortality and complications, including sepsis, reoperations, and readmissions. Preoperatively, the elderly cohort also had higher rates of comorbidities, including sleep apnea, gastroesophageal reflux disease, and hypertension. After controlling for all variables, multivariate logistic regression analysis revealed that being pediatric, male, or having a preoperative body mass index (BMI) ≥45 kg/m2 were associated with a BMI decrease of ≥2.5 kg/m2 postoperatively within the 30-day follow-up period. Conclusion : These findings highlight the varying clinical outcomes among age groups of patients undergoing bariatric surgery. The pediatric cohort saw the most significant decrease in postoperative BMI with minimal complications, while the elderly cohort saw the opposite trend.